Moderation as Cultural Negotiation: Islamic Business Ethics and Local Value Integration in Indonesian Chinese Muslim Micro, Small, and Medium Enterprises (MSMEs) - Mukhoyyaroh, Mukhoyyaroh; Hasanah, Yenny Merinatul; Bidayaturrohmah, Afifah; Fadilah, Kaida (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
This study explores the implementation of religious moderation within Chinese Muslim MSMEs in Jakarta. Employing a qualitative case study approach, data were collected through observation and in-depth interviews with three purposively selected Chinese Muslim entrepreneurs. Unlike prior studies, this research applies the framework of religious moderation to analyze Islamic business ethics in harmony with local cultural values. The findings reveal that Chinese Muslim MSMEs effectively integrate Islamic principles with traditional Chinese virtues, such as birr al-wālidayn and xiao, emphasizing filial piety as foundational ethical values. These values shape business practices that are fair, humane, and socially responsible. The study demonstrates that religious moderation can be expressed through daily business conduct, fostering tolerance, respect, and cross-cultural understanding. The integration of Islamic teachings and Chinese traditions offers a model for inclusive and sustainable business environments. Ultimately, this research contributes to broader efforts in promoting religious moderation and multicultural coexistence in economic practices.